An Evaluation of the Longitudinal, Bidirectional Associations Between Gait Speed and Cognition in Older Women and Men - Best, John R; Liu-Ambrose, Teresa; Boudreau, Robert M; Ayonayon, Hilsa N; Satterfield, Suzanne; Simonsick, Eleanor M; Studenski, Stephanie; Yaffe, Kristine; Newman, Anne B; Rosano, Caterina (The journals of gerontology. Series A, Biological sciences and medical sciences, 2016)
Few cohort studies have examined longitudinal associations between age-related changes in cognition and physical performance. Further, whether these associations differ for men versus women or can be attributed to differences in physical activity (PA) is unknown. Participants were 2,876 initially well-functioning community-dwelling older adults (aged 70-79 years at baseline; 52% female; 39% black) studied over a 9-year period. Usual gait speed, self-reported PA, and two cognitive measures-Digit Symbol Substitution Test (DSST) and Mini-Modified Mental State examination (3MS)-were assessed years 0 (ie, baseline), 4, and 9. Early decline between years 0 and 4 in gait speed predicted later decline between years 4 and 9 in performance on the 3MS (β = 0.10, p = .004) and on the DSST (β = 0.16, p < .001). In contrast, the associations between early decline in cognition and later decline in gait speed were weaker and were non-significant after correcting for multiple comparisons (β = 0.08, p = .019 for 3MS and β = .06, p = .051 for DSST). All associations were similar for women and men and were unaltered when accounting for PA levels. The results indicate declining gait speed as a precursor to declining cognitive functioning, and suggest a weaker reciprocal process among older women and men.